Comparison of open vs Plastibell techniques of circumcision for surgical outcomes and cosmetic satisfaction;A randomized control trial - Iqbal, Muhammad; Ijaz, Sadaf; Zafar, Muhammad Hassan; Malik, Naveed Akhtar (Journal of Rawalpindi Medical College, 2022)
Objective of the study: To compare the results of circumcision by open technique and the Plastibell technique in male babies. Methods: In this randomized controlled interventional study, 1440 babies whose circumcision was done as religious rite were divided into two groups. Group A underwent circumcision by open technique whereas group B underwent circumcision by Plastibell method. Results: Majority 720 (50%) were in age group 6-8 weeks. Compared with open method, significantly less number of patients in plastibel method experienced moderate pain (47.91% versus 35% p value .00001 and severe pain 31.94% versus 9.02% p value .00001.Rate of wound infection was significantly less in plastibell method 2.77% versus 4.86% p value .020. However more patients in plastibell technique needed re-do circumcision 4.02% versus 1.94% p value .0202. Overall greater parent’s satisfaction was attained with plastibel method. Conclusion: Plastibell technique has many advantages over open method in terms less post op pain, wound infection, and greater cosmetic satisfaction however more patients will need re-do circumcision in this technique compared with conventional method. Keywords: Circumcision, open technique, Plastibell, post-op complications